Applications of hydrocolloids and its effects on physicochemical characteristics of gluten-free bread from corn and rice flour - Fetriyuna, Fetriyuna; Agustinisari, Iceu; Kurniasari, Indah; Hastuti, Novitri; Eris, Fitria Riany; Kusnandar, Feri; Bachtiar, Muchamad; Fetriyuna, Fetriyuna (Penerbit Universiti Kebangsaan Malaysia, 2024)
Rice and corn flour can be used for gluten-free bread using a number of food hydrocolloids to improve the physicochemical properties closer to wheat products. This research aims to observe the effect of different types of food hydrocolloids, namely xanthan gum, glucomannan, carrageenan and CMC (Carboxymethyl Cellulose) on the physicochemical characteristics of gluten-free bread made from rice and corn flour. This research used a completely randomized design with two replications. This research observed the application of hydrocolloids to the formulation of gluten-free bread. The optimal increase in hydrocolloid concentration was determined to be 1 g for both CMC and carrageenan in both corn and rice flour. The highest addition of 1 g CMC in gluten-free bread made from corn flour, resulted in a specific volume of 3.422 cm3 /g. The best gluten-free corn bread after drying contains a composition of 5.73% moisture content, 1.89% ash content, 17.34% fat content, 9.37% protein content, 65.67% carbohydrate content, and energy of 456.22 Kcal.